2005
DOI: 10.1108/14769018200500034
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Integrating Medical and Social Care: Five Laws Revisited

Abstract: This paper reviews, rethinks, expands and applies the author's 'laws' of integration, which were first published six years ago. This approach both introduces the laws to readers who don't know them, and tests their utility for those who do. In retrospect, real-world integration efforts mix and match the original components of linkage, coordination and full integration. But the message remains to work at all levels, keep it simple, make finances supportive and empower social care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 16 publications
(11 reference statements)
6
68
0
Order By: Relevance
“…Each of the sequential models proposed a number of stages or progressions from less coordinated care to a fully integrated healthcare system [5, 52, 56]. …”
Section: Resultsmentioning
confidence: 99%
“…Each of the sequential models proposed a number of stages or progressions from less coordinated care to a fully integrated healthcare system [5, 52, 56]. …”
Section: Resultsmentioning
confidence: 99%
“…This project has shown that a capacity-building approach to research and evaluation can also mediate tensions between top-down initiatives and on-the-ground practitioners. Leutz's (2005) recent review of his five laws for integrating medical and social care points out that it is up to those with the authority to design an integration programme to hand out power and resources to empower people who share the goals of the programme to take the integration forward. He also notes that all integration is local.…”
Section: Resultsmentioning
confidence: 99%
“…• linkage (informal relationship between service providers that is enacted as needed) • collaboration (two or more services work together usually in relation to shared patient care for which there is usually formal or standardised information sharing) • co-ordination (relationships between services are more formalised and there is evidence of shared planning, delivery and evaluation of care in relation to mutually agreed goals) • integrated (characterised by pooled funding, sharing of resources and joint programmes) (Alexander, 2001;Leutz, 1999;Leutz, 2005;Reynolds et al, 2001). …”
Section: The Projectmentioning
confidence: 99%
“…Many of these services conditions. An annual publication and conference in the UK has publicised these services (Community Hospitals Association, 2000-2005. Table 1 provides examples of vertical and horizontal integrated services in England, with the mechanism facilitating the development of integration listed.…”
Section: Integration and Innovationmentioning
confidence: 99%